2015
DOI: 10.1007/s10495-015-1190-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of apoptosis and necroptosis inhibitors in cisplatin-induced nephrotoxicity

Abstract: Necroptosis is a nonapoptotic cell death pathway. We aim to study the effect of necrostatin-1 (a specific necroptosis inhibitor) in cisplatin-induced injury. We analyzed the effect of the combined use of inhibitors of apoptosis (z-vad) and necroptosis (necrostatin-1) in acute kidney injury by cisplatin in human proximal tubule cells. Our results showed moderate effectiveness in cytoprotection after treatment with z-vad. But the concomitant use of inhibitors (z-vad and necrostatin-1) presented synergistic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Signs of an ongoing necroptotic response (e.g., increased RIPK1, RIPK3, and/or MLKL expression and/or phosphorylation levels) are common to various renal disorders (at least in mice), including acute kidney injury (AKI) caused by I/R (115, 119, 162), urolithiasis (163), cisplatin-based chemotherapy or radiocontrast (115, 164167), and chronic kidney disease after unilateral nephrectomy (168). Nec-1 mediates nephroprotective effects in virtually all these settings, which supports the contention that necroptosis contributes to the etiology of various renal disorders, at least in mice.…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Signs of an ongoing necroptotic response (e.g., increased RIPK1, RIPK3, and/or MLKL expression and/or phosphorylation levels) are common to various renal disorders (at least in mice), including acute kidney injury (AKI) caused by I/R (115, 119, 162), urolithiasis (163), cisplatin-based chemotherapy or radiocontrast (115, 164167), and chronic kidney disease after unilateral nephrectomy (168). Nec-1 mediates nephroprotective effects in virtually all these settings, which supports the contention that necroptosis contributes to the etiology of various renal disorders, at least in mice.…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
“…Similar data were obtained with Nec-1, SfA, and 16–86, employed alone or in combination (115, 165), which suggests that various forms of necrotic RCD contribute to the etiology of AKI. Some authors report that Z-VAD-fmk can enhance the nephroprotective effects of Nec-1 in models of cisplatin-induced AKI (164, 167), whereas others demonstrate that Z-VAD-fmk has no beneficial effects in mice experiencing radiocontrast- or I/R-driven AKI (162, 165). This apparent discrepancy may stem from the capacity of cisplatin to trigger apoptotic RCD in some tubule cells and necroptosis in others.…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
“…Injecting radiocontrast medium 24 h after IR induced further contrast-induced AKI, a type of injury also reversible with Nec-1 [6]. Two independent groups consistently reported that Nec-1 attenuates tubular cell injury in cisplatin-induced AKI in mice [7, 8]. Another group reported Nec-1 to attenuate rhabdomyolysis-induced AKI triggered by intramuscular injection of glycerol [9].…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
“…High RIPK3 expression may facilitate the aggregation of RIPK3 oligomers to a higher-order structure (referred to as the necrosome) that induces MLKL phosphorylation. [9][10][11][12] Ferroptosis is an iron-dependent regulated necrosis subroutine characterized by increased lipid peroxidation resulting from lack of activity of the glutathione peroxidase 4 that requires glutathione to function. Necroptosis is an important contributor to tissue injury in the heart, skin, and intestine, but its contribution to renal injury is incompletely characterized.…”
mentioning
confidence: 99%